Expression of Concern: Potential Risks and Unknown Effects of mRNA Vaccines on Population Health (6th Rev). Damages Are Being Materialized - Jianqing, Wu (International Journal of Coronaviruses, 2022)
Several mRNA vaccines are used on the population in the U.S. I started predicting the dangers of mRNA vaccines before March 2021 and update my findings periodically. My prior model study enabled me to identify many flaws in clinical trials, side-effect evaluation methods and mechanism studies, and I also considered consistent failure in predicting drug side effects in the past and systematic failure of FDA in keeping out dangerous drugs from market. I found that the risks of vaccination cannot be determined by experiments alone and must be determined by using a combination of methods. By studying mRNA expression dynamics and kinetics, I predict that vaccination with mRNA vaccines may increase cancer risks, multiple organ failure risks, earlier death risks, genome alteration speeds by one or more mechanisms, alter the normal selection process for viral evolution resulting in more virulent viruses, and aggravate chronic diseases or cause healed diseases to relapse. Two root problems are practical inability to control expression sites and severe adverse reactions from repeated vaccination. Based on mRNA bio-distribution, the mRNA mainly strikes the liver and other vital organs, and poses grave dangers to persons whose vascular functional reserves are relatively small, or whose vascular systems are temporarily burdened by other causes such as viral infections or life activities. If an mRNA vaccine is administered on a pregnant woman by second or booster shots, spike protein synthesis in fetus brain disrupts the highly regulated protein synthesis processes, resulting in potential brain damages. In less than a year, most of my early predicted damages are being materialized or are on the track to hit the population. In this update, I present a benefits-and-risks map to show how the number of deaths caused by mRNA vaccines is grossly underestimated and why claimed benefits like 95% effectiveness rate and 90% death rate reduction are meaningless and misleading.
Keywords: mRNA vaccines; SARS-CoV-2; COVID-19; coronavirus; population vaccination; vaccine risks